Pewarisan Pengetahuan Lokal Jamu dalam Masyarakat Kampung Tematik - Fike Windi Nufria Wati; Mutiatus Soleha; suci anjani (Dimensia: Jurnal Kajian Sosiologi, 2026)
The author would like to express his gratitude to Allah subhanahu wa ta'ala for the completion of this research. The author also expresses his deepest appreciation and gratitude to various parties who have contributed and helped in the writing of this article, to Mr. Harto Wicaksono as the supervising lecturer who has provided direction, guidance and input in the preparation of this article until completion, to the head of the RT and all residents of Sumbersari Hamlet, Wonolopo Village for the permission and willingness that has been given during the data collection process in the field, the head and secretary of the Sumber Husada herbal medicine association for the availability of various historical data in the herbal medicine thematic village, the herbal medicine craftsmen who have shared their knowledge regarding the production process to herbal medicine marketing strategies, and all parties who have provided moral and material support so that this research can be completed well. Hopefully this article can benefit the development of science and become a reference in the preservation of local wisdom in Indonesia